Moderni dokumentni sistemi - Reja, Dimitrij (Atlanti, 2023)
Purpose: An overview of the use of a modern document system in practice. Methode/approach: Overview of the user experience when using the document system Results: General overview of use in the field of archival science. Conclusions/findings: New systems for managing documentary material offer us a wide variety of possibilities for organizing and planning work in organizations.
Keywords: algorithm; algoritmo; archival sciences; arhivske znanosti; dokumentni sistemi; machine learning; scienze archivistiche